Hydrocarbon accumulation model influenced by “three elements (source-storage-preservation)” in lacustrine shale reservoir-A case study of Chang 7 shale in Yan’an area, Ordos Basin - Wang, Xiangzeng; Liang, Quansheng; Gao, Chao; Xue, Pei; Yin, Jintao; Hao, Shiyan (Frontiers in Earth Science, 2022)
The organic-rich shale of Chang 7 Member of Yan'an Formation in Yan'an area of Ordos Basin is a hot spot for lacustrine shale gas exploration. In this paper, taking the Chang 7 Member shale in the Yan'an area as an example, the main controlling factors of lacustrine shale gas accumulation and the prediction of "sweet spots" are systematically carried out, based on a large number of geochemical and reservoir characterization experiments. The results show that the Yanchang Formation shale has the basic gas generating conditions for shale gas formation. Shale gas accumulation requires three necessary accumulation elements, namely gas source, reservoir and good preservation conditions. The dynamic hydrocarbon generation process of shale reservoirs is established according to the thermal simulation experiment of hydrocarbon generation, and the mechanism of catalytic degradation and gas generation in Chang 7 Member under the background of low thermal evolution is revealed. The enriched authigenic pyrite can catalyze the hydrocarbon generation of organic matter with low activation energy, thereby increasing the hydrocarbon generation rate in the low-mature-mature stage. Different types of pores at different scales form a multi-scale complex pore network. Free gas and dissolved gas are enriched in laminar micro-scale pores, and adsorbed gas is enriched in nano-scale pores of thick shale, and silty laminae can improve the physical properties of the reservoir. The thickness of lacustrine shale in Chang 7 Member is 40-120 m, which exceeds the effective hydrocarbon expulsion thickness limit (8-12 m) in the study area. At the end of the Early Cretaceous, the excess pressure of the Chang 7 shale was above 3MPa. At present, horizontal wells with a daily gas production of more than 50,000 cubic meters are distributed in areas with high excess pressure during the maximum burial depth.